Disrupted Thalamus White Matter Anatomy and Posterior Default Mode Network Effective Connectivity in Amnestic Mild Cognitive Impairment - Alderson, Thomas; Kehoe, Elizabeth; Maguire, Liam; Farrell, Dervla; Lawlor, Brian; Kenny, Rose A.; Lyons, Declan; Bokde, Arun L. W.; Coyle, Damien (Frontiers in Aging Neuroscience, 2017)
Alzheimer’s disease (AD) and its prodromal state amnestic mild cognitive impairment (aMCI) are characterised by widespread abnormalities in inter-areal white matter fibre pathways and parallel disruption of default mode network (DMN) resting state functional and effective connectivity. In healthy subjects, DMN and task positive network interaction are modulated by the thalamus suggesting that abnormal task-based DMN deactivation in aMCI may be a consequence of impaired thalamo-cortical white matter circuitry. Thus, this paper uses a multimodal approach to assess white matter integrity between thalamus and DMN components and associated effective connectivity in healthy controls (HC) relative to aMCI patients. Twenty-six HC and 20 older adults with aMCI underwent structural, functional and diffusion MRI scanning using the high angular resolution diffusion-weighted acquisition protocol. The DMN of each subject was identified using independent component analysis and resting state effective connectivity was calculated between thalamus and DMN nodes. White matter integrity changes between thalamus and DMN were investigated with constrained spherical deconvolution tractography. Significant structural deficits in thalamic white matter projection fibres to posterior DMN components posterior cingulate cortex (PCC) and lateral inferior parietal lobe (IPL) were identified together with significantly reduced effective connectivity from left thalamus to left IPL. Crucially, impaired thalamo-cortical white matter circuitry correlated with memory performance. Disrupted thalamo-cortical structure was accompanied by significant reductions in IPL and PCC cortico-cortical effective connectivity. No structural deficits were found between DMN nodes. One interpretation is that abnormal posterior DMN activity is driven by changes in thalamic white matter connectivity; a view supported by the close anatomical and functional association of thalamic nuclei effected by AD pathology and the posterior DMN nodes. We suggest that impaired cortico-thalamo-cortical processing, is to some extent, mediating the reduced coordination between distributed cortical networks in aMCI. One supposition, is that disease agents originating in the hippocampus are transmitted in a prion-like manner through thalamus to posterior cortical nodes PCC and IPL, initiating the well-documented cascade of structural and functional anomalies observed in DMN elements.